2015
DOI: 10.1109/mcas.2015.2450635
|View full text |Cite
|
Sign up to set email alerts
|

Towards Multi-Domain and Multi-Physical Electronic Design

Abstract: Electronic systems are increasingly fusing multiple technology solutions exchanging information both at electrical and at nonelectrical levels, and in general both analog and digital operation coexists in multiple physical domains. this paper introduces a homogeneous multi-domain design methodology which blurs analog and digital boundaries and enables the design of etherogeneous electrical and non-electrical building blocks. the methodology is based on the identification of four fundamental quantities (quadriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…Most sensors, except those for light or radar, can be classified into four types: voltage, current, resistive, and capacitive [15], [16]. Recent research reviews have shown that environmental sensors are mostly resistive or capacitive [17] and conventional healthcare sensors are typically measured based on voltage or current [18].…”
Section: Multi-sensor System Architecturementioning
confidence: 99%
“…Most sensors, except those for light or radar, can be classified into four types: voltage, current, resistive, and capacitive [15], [16]. Recent research reviews have shown that environmental sensors are mostly resistive or capacitive [17] and conventional healthcare sensors are typically measured based on voltage or current [18].…”
Section: Multi-sensor System Architecturementioning
confidence: 99%
“…The analog front-end circuit plays a vital role in sensor application systems, serving as a bridge between sensors and digital systems. It converts signals from various types of sensors (resistive/capacitive/voltage/current) [4,5] into voltage signals, which are then amplified and transmitted [6,7]. In the quest for developing sensor application systems, numerous configurations have been employed for the analog front-end circuit.…”
Section: Introductionmentioning
confidence: 99%